2015
DOI: 10.1007/s13592-015-0375-9
|View full text |Cite
|
Sign up to set email alerts
|

European isolates of the Microsporidia Nosema apis and Nosema ceranae have similar virulence in laboratory tests on European worker honey bees

Abstract: -Nosema apis and Nosema ceranae are gut parasites that infect western honey bees (Apis mellifera ) worldwide. N. ceranae is an exotic infectious disease agent of A. mellifera , having been originally described in the Asian honey bee (Apis cerana ), while N. apis is native to the western honey bee. To better understand the dynamics and epidemiology of the two pathogens, we examined the impact of European isolates of both Microsporidia on the longevity of European A. mellifera in a controlled laboratory experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…A first study of the within-host competition effect between N. apis and N. ceranae did not show any clear competitive advantage for any of them (Forsgren and Fries 2010). However, a later study identified a priority effect when N. ceranae was the first infection (Natsopoulou et al, 2016). Apparently both environmental variables and interspecies competition are important elements of mathematical models that help explain the differential prevalence of Nosema spp.…”
Section: How Is Nosema Transmitted?mentioning
confidence: 99%
“…A first study of the within-host competition effect between N. apis and N. ceranae did not show any clear competitive advantage for any of them (Forsgren and Fries 2010). However, a later study identified a priority effect when N. ceranae was the first infection (Natsopoulou et al, 2016). Apparently both environmental variables and interspecies competition are important elements of mathematical models that help explain the differential prevalence of Nosema spp.…”
Section: How Is Nosema Transmitted?mentioning
confidence: 99%
“…The ectoparasitic mite Varroa destructor and the viruses it transmits, particularly deformed wing virus (DWV), are considered the major cause of elevated honey bee mortality [34,35,36,37,38,39,40,41]. Over the last two decades, the emerging microsporidium Nosema ceranae has also become prevalent globally and has been shown to cause honey bee mortality [42,43,44], although the extent to which it is responsible for colony loss has been debated [45,46]. More recently, the wider risk posed by N. ceranae to sympatric wild bee populations has been explored, with studies revealing transmission of the parasite to bumble bees [47,48,49] and solitary bees such as Osmia bicornis [50].…”
Section: Introductionmentioning
confidence: 99%
“…Microsporidia N. apis Zander, 1909, responsible for type A nosemosis, is a globally distributed parasite specific for the European honeybee, Apis mellifera L. (Zander, 1909). N. apis was for years considered to be the only disease agent of nosemosis in honeybee A. mellifera (Bailey, 1955;Natsopoulou et al, 2015). N. ceranae Fries et al, 1996, responsible for type C nosemosis, was first described in Asian honeybee, Apis cerana Fabricius, at the end of the twentieth century (Fries et al, 1996) and later in honeybees A. mellifera worldwide (Fries et al, 2006;Higes et al, 2006Higes et al, , 2009Higes et al, , 2010aHuang et al, 2007;Klee et al, 2007;Martin-Hernandez et al, 2007;Chen et al, 2008Chen et al, , 2010Williams et al, 2008;Invernizzi et al, 2009;Fries, 2010;Yoshiyama & Kimura, 2011;Medici et al, 2012;Ostroverkhova et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%